Pengaruh Faktor-Faktor Manajemen Mutu Terpadu dan Rekayasa Kualitas Proses Bisnis Agar Tercapainya Intention Customer PO Dengan Moderasi : (Studi pada Pt. Indofood pada Produk Susu Kental Manis) - Rafi’ah Kumalasari; Suci Fathimah Rizaldy; Gina Aulia Dewi; Septiana Dewi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the influence of factors from Integrated Quality Management and Business Process Quality Engineering to achieve Intention Customer PO. Respondents from this study were 61 respondents and this study used a quantitative approach. Integrated Quality Management or Total Quality Management (TQM) and Business Process Quality Engineering or Business Process Reengineering (BPR) are two strategic approaches and can be used synergistically to achieve Customer Purchase Order (PO) fulfillment with high efficiency and effectiveness. This research examines the influence of implementing Total Quality Management (TQM) and business process quality engineering on customer intention to repurchase (intention customer PO) for sweetened condensed milk products at PT. Indofood. The research results show that the implementation of TQM and business process quality engineering together can increase intention customer PO. Increased customer satisfaction is a crucial factor in achieving intention customer PO. This research contributes to PT. Indofood by providing an understanding of the importance of implementing TQM and business process quality engineering in achieving intention customer PO, providing empirical data to develop more effective marketing strategies, and providing recommendations to improve product and service quality, as well as customer satisfaction